2018
DOI: 10.1002/1878-0261.12408
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5‐mediated deacetylation of LDHB promotes autophagy and tumorigenesis in colorectal cancer

Abstract: Lactate dehydrogenase B (LDHB) is a glycolytic enzyme that catalyses the conversion of lactate and NAD + to pyruvate, NADH and H+. Protons (H+) generated by LDHB promote lysosomal acidification and autophagy in cancer, but how this role is regulated has not been defined. In this study, we identified an important post‐translational mechanism by which LDHB is regulated during autophagy in cancer cells. Mass spectrometry revealed that protein sirtuin 5 (SIRT5) is a binding partner of LDHB that deacetylated LDHB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 49 publications
2
88
0
Order By: Relevance
“…7B). Although LDH exists as five different isoenzymes, 31,32 . Interestingly, we found that whereas LDHB is not expressed in liver, it is highly expressed in the GIT, including the cecum ( Fig.…”
Section: Analysis Of Plga-relevant Transcriptional Pathways In Human mentioning
confidence: 99%
“…7B). Although LDH exists as five different isoenzymes, 31,32 . Interestingly, we found that whereas LDHB is not expressed in liver, it is highly expressed in the GIT, including the cecum ( Fig.…”
Section: Analysis Of Plga-relevant Transcriptional Pathways In Human mentioning
confidence: 99%
“…Hence, altered expression of LDHC could be involved in maintaining an alternative energy source by contributing to the metabolic switch in cancer cells. In addition, increased LDHA and decreased LDHB expressions facilitate tumor formation and progression through remodeling of the tumor microenvironment, increasing proliferation, and inducing epithelial-to-mesenchymal transition, cell migration and invasion, and angiogenesis [10][11][12][13][14][15][16][17][18][19][20]. In line with this, two studies to date demonstrate that enhanced expression of LDHC induces epithelial-to-mesenchymal transition, matrix metalloproteinase-9 (MMP9) expression and promotes cancer cell migration and invasion [7,21].…”
Section: Introductionmentioning
confidence: 81%
“…As an important glycolytic enzyme, LDHB has been reported to be overexpressed in triple-negative breast cancer [21] and promote the tumorigenesis of colorectal cancer [22]. Although LDHB has been confirmed to express at a high level in OS cells [23], the functional role and molecular mechanism of LDHB have not been researched in OS.…”
Section: Discussionmentioning
confidence: 99%